American city St. Louis architecture : three centuries of classic design - Sharoff, Robert; Zbaren, William (Mulgrave, Vic., Australia The Images Publishing Group, 2010)
Features Louis Sullivan's Wainwright Building, Alfred Mullet's Old Post Office and Theodore Link's Union Station, Eero Saarinen's Gateway Arch, Tadao Andao's Pulitzer Foundation for the Arts Building and Maya Lin's recently completed Ellen Clark Hope Plaza.
Machine generated contents note: Old Courthouse -- Missouri Botanical Garden Museum and Library -- Grand Avenue Water Tower -- Eads Bridge -- Raeder Place -- Linnean House -- Old Post Office -- Isaac H. Lionberger House -- Merchandise Mart -- Bell Telephone Building -- Anheuser-Busch Brew House -- Wainwright Building -- Wainwright Tomb -- St. Louis Union Station -- Washington Terrace Entrance Gate -- Bee Hat Building -- Chemical Building -- Compton Hill Water Tower -- St. Louis University Museum of Art -- Flight Cage -- St. Louis Art Museum -- St. Louis City Hall -- Patrick Henry School -- Roberts, Johnson & Rand Shoe Company Building -- Municipal Courts Building -- St. Louis Public Library -- Intake Tower #2 -- Missouri Athletic Club -- Southwestern Bell Building -- Continental Building -- Fox Theater -- Civil Courts Building -- Tums Building -- Jewel Box -- Grant Clinic -- Milles Fountain -- Lambert Field Main Terminal -- Steinberg Hall -- Climatron -- James S. McDonnell Planetarium -- Gateway Arch -- American Zinc, Lead & Smelting Company Building -- Pet Plaza -- General American Life Building -- 1010 Market -- One AT&T Center -- Pulitzer Foundation for the Arts at BJC Institute of Health -- Mildred Lane Kemper Art Museum -- Centene Plaza -- Ellen S. Clark Hope Plaza.
Reprinted in 2012.
Includes bibliographical references (p. 133) and indexes.
AIT-4252g from the collection of Ivan Anthony S. Henares, Asian Institute of Tourism, University of the Philippines.
Keywords: Architecture -- Missouri -- Saint Louis; Architecture -- Missouri -- Saint Louis -- Pictorial works; Saint Louis (Mo.) -- Buildings, structures, etc; Saint Louis (Mo.) -- Buildings, structures, etc. -- Pictorial works